SPOSITO, E. BOMTEMPO, D. & SOUZA, A. (org.) Geografia e migração. Movimentos, territórios e territorialidades. 1ª Ed. São Paulo, Expressão Popular, 2010. - Marafon, Glaucio Jose (Geo UERJ, 2010)
doi: 10.12957/geouerj.2010.1466